“I'm luckier than everybody else!”: Optimistic bias, COVID-19 conspiracy beliefs, vaccination status, and the link with the time spent online, anticipated regret, and the perceived threat - Maftei, Alexandra; Petroi, Cosmina Elena (Frontiers in Public Health, 2022)
The catastrophic wave in the fall of 2021 drove Romania to the top of the list of dangerous COVID-19 infections, with the highest mortality rate in Europe. At the same time, Romania had one of the lowest vaccination rates. In this context, the present research aimed to explore the link between vaccination intention/status, optimistic bias, COVID-19 conspiracy beliefs, the time spent online, and vaccination (anticipated) regret. Our convenience sample was formed by 408 adults aged 18–63 years (M = 22.11, SD = 6.18, 69.9 % females), who were distributed into four groups: (1) non-vaccinated who definitely refused COVID-19 vaccination, (2) non-vaccinated who considered COVID-19 vaccination, (3) non-vaccinated who reported their absolute willingness to COVID-19 vaccination, and (4) people who were COVID-19 vaccinated. We conducted our analyses separately, depending on these groups (i.e., vaccination intentions/status). Data were collected using an online questionnaire between November 10, 2021, and January 03, 2022. In our cross-sectional approach, following correlation and ANOVA analyses, among the observed patterns were (1) the significant negative relation between optimism bias and the perceived COVID-19 threat; (2) the positive link between anticipated regret, post-vaccination regret, age, and conspiracy beliefs. We discuss our findings considering their contribution to health policies and practices.